Cuidado desenvolvimental e práticas de enfermeiras de Unidades de Terapia Intensiva Neonatal: busca por processos crítico-reflexivos - Facio, Beatriz Castanheira (2019)
Assistance to the newborn, child, adolescent and family has undergone transformations and currently faces the challenge of aligning with developmental care (DC). Given the need for support from families to cope with the reality of having a child in a neonatal intensive care unit (NICU), and the growing identification that training can contribute to the advance in care practices, this study aims to discuss the repercussions of the formative process in developmental care on the practices of NICU nurses in a city in the interior of São Paulo. The specific objective is to report on the development of a formative intervention on developmental care with NICU nurses in a city in the interior of São Paulo, with attention to participation movements. It is an interpretative and longitudinal research, anchored in 3 theoretical references: “Nursing as care”, by Anne Boykin and Savina Schoenhofer; “The Nursing Knowledge Standards”, by Barbara Carper; and “Reflective Teaching and Practice”, by Donald Schön. Appreciative Research is the methodological framework used. Due to the awarness that the nursing coordinators of two NICUs in this municipality were involved in qualification of the nursing care provided, contact was sought with a view to identifying nuclei of common interest, when the DC was revealed. The criteria for selecting participants included to be a nurse working in at least one of the neonatal units in the city. There was an oscillation in the number of participants, with differences in the collection and intervention phases. The first included non-participant observation and semi-structured interviews as strategies, which were preceded by written activity. After this activity, a discussion about the topic was proposed. The intervention was based on the 4D cycle, the acronym used to designate the phases Discovery, Dream, Design and Destiny. Data analysis was based on the Minayo Thematic Content Analysis and allowed the emergence of three blocks: Guiding principles of NICU nurses practices; 4D cycle management in the development of educational intervention; Participation movements in the face of proposals and strategies offered in educational intervention. The first block was divided into two categories: “Promoting newborn development and comfort” and “Qualifying NICU care”. In the second one, the results from the 4D cycle analysis were evidenced, encompassing the unit dynamics management and developmental care offer, strategies suggested by the participants and the consequence of lived limitations. Finally, the third block explains the different strategies used to achieve reflective participation of nurses. Faced with insufficient interactions and discussions without the desired deepening, it was reflexively problematized about the possible causes: driving mode; influence of training, the current health care model and the obstacles experienced in the work context. With attention to deepening morals, we considered motivation, responsibility, commitment, respect and solicitude in nursing care. It is suggested that further studies explore what hospital managers think about training processes, paying attention to their place of relevance, their assigned values and what they mean by support.